居住水準向上と住環境保全を両立させる地域地区見直し方法に関する研究(2) - 高見沢 実; 和多 治; 小泉 秀樹; 勝又 済; 町田 弘一 (住宅総合研究財団研究年報, 1993)
This study is based upon an evaluation of continuous research into the impact of easing use district regulations for suburban residential areas of Tokyo wards ; (the rezoning of its use districts was announced on October 11th, 1989), and it is a sequel to earlier research carried out in Yokohama (announced on October 29th, 1985) and Kawasaki (announced on September 29th, 1987). First classified under the history of forming suburban residential areas of Tokyo wards (type I exclusive district for residential use), we subsequently categorized the material into types of urban districts especially from the point of view of rezoning for use districts. As a result, the following four types were listed: 1) residential areas originally close to the center part and which had floor area restrictions of 150% (this restriction was relaxed to 200% following the new format: 2) residential areas, whose original 80% restriction was relaxed to 100%: 3) those residential areas which originally had a 60% restriction and through an easing of the restriction for the older green areas the restriction was related to 100% by the rezoning of the time: 4) those residential areas where easing of restrictions were done in parallel with the designation of a new district plan. 1)-3) can be seen typically in Nerima Ward, and 4) can be seen occasionally in Setagaya Ward. In this study, which focused on Nerima Ward for the reason that it's a typical suburban residential area of Tokyo and the restrictions were relaxed on a large scale, we established two typical areas, then made and distributed a questionnaire. As a result, the facts emerged that; there were quite a number of illegal constructions in the districts where the restrictions have so far been strict : and in the districts whose floor area ratios were relaxed to 150%, the characteristics as a residential area for detached houses have changed by land subdivision and by apartment-house building owing to inheritance: the fact that relaxation has promoted the change is clear. 本研究は，これまでに実施した横浜市(1985年10月29日，用途地域見直し告示）・川崎市（同1987年9月29日）調査の続編として，東京区部（同1989年10月2日）郊外住宅地の用途地域緩和の影響に関する調査を継続して行なった結果である。まず，東京区都郊外住宅地（第一種住居専用地域）の形成の歴史を整理し，そうした市街地の類型化を特に用途地域見直しの視点から行なった。この結果，1)もともと中心部に近く150％の容積規制が行なわれていたが，新メニューの登場により200％の容積規制に緩和された住宅地，2)もともと80％の容積規制が100％に緩和された住宅地，3)旧緑地地域の規制緩和で容積率60％か指定されていたが，今回の見直しで100％に規制緩和された住宅地，4)規制緩和が行なわれたが，地区計画指定が並行してなされた住宅地，の4類型が得られた。1)～3)は練馬区に典型的にみられ，4)は世田谷区に若干みられる。本研究では，東京都外住宅地の典型であること，及び規制緩和が大幅に行なわれたことを理由に練馬区に焦点を絞り，2つの典型地区を設定してアンケート調査を実施した。その結果，これまで規制が厳しかった地区では違法建築がかなり存在しており，さらなる緩和の予備軍となっていること，150％に容積率が緩和された地区では相続による分割，アパート化等で戸建住宅地としての性格が変化しており，緩和はその変化を助長していること，などがわかった。